Evidence‐based Management in Practice: Opening up the Decision Process, Decision‐maker and Context. (28th September 2015) - Wright, April L.; Zammuto, Raymond F.; Liesch, Peter W.; Middleton, Stuart; Hibbert, Paul; Burke, John; Brazil, Victoria
Abstract : Evidence‐based management (EBM) has been subject to a number of persuasive critiques in recent years. Concerns have been raised that: EBM over‐privileges rationality as a basis for decision‐making; 'scientific' evidence is insufficient and incomplete as a basis for management practice; understanding of how EBM actually plays out in practice is limited; and, although ideas were originally taken from evidence‐based medicine, individual‐situated expertise has been forgotten in the transfer. To address these concerns, the authors adopted an approach of 'opening up' the decision process, the decision‐maker and the context (Langley et al . (1995 ). 'Opening up decision making: the view from the black stool', Organization Science, 6, pp. 260–279). The empirical investigation focuses on an EBM decision process involving an operations management problem in a hospital emergency department in Australia. Based on interview and archival research, it describes how an EBM decision process was enacted by a physician manager. It identifies the role of 'fit' between the decision‐maker and the organizational context in enabling an evidence‐based process and develops insights for EBM theory and practice.